HOW TO INTEGRATE XBRL INTO ACCOUNTING CURRICULUM AT BANJARMASIN STATE POLYTECHNIC - Rahwani, Noor Romy (INTEKNA, 2013)
The purpose of this research is to develop accounting curriculums for Banjarmasin State Polytechnic (POLIBAN). The curriculums integrate the XBRL (eXtensible Business Re-porting Language) materials into their course designs. The ideal XBRL related curriculum was developed based on the course designs recommended by Debreceny and Farewell (2011). In the recommended course design, the coverage of XBRL builds in the ac-counting curriculum the same way that the breadth and depth of accounting concepts in-creases.However, when it comes to the implementation, there are some main barriers that should be taken into account i.e.Â  (1) Not all lecturers understand well about XBRL as the XBRL is relatively new topic to most of the accounting lecturers. (2) As Indonesia GAAP Ta-xonomy has not been developed, it means that there will be no real case studies related to this taxonomy that can be developed.Â  (3) Developing a good XBRL related syllabus should take time. Based on those impediments, the applicable accounting curriculums that integrate the XBRL were then designed for academic year 2011/2012 via curriculum development workshop. In the Computerized Accounting Study Program, the subjects that cover the XBRL materials are Management Information System, Accounting Information System II, and Internet/Web-based Programming. In the Regular accounting Study Program, the subjects that cover the XBRL materials are âCurrent Issue in Accountingâ The subsequent academic years (after 2011/2012), the XBRL related course design in previous academic years has to be evaluated and enhance. The accounting Department has better apply the suggestions discussed in the last chapter, so the XBRL related cour-se design recommended by Debreceny and Farewell (2011) will be eventually achieved.